Solid pseudopapillary neoplasms-experience from a tertiary care centre - Madhusudhan Chinthakindi; Kyyoda Prashanth; Jyothiprakasham Vinod Kumar; Ramalingam Pratap Reddy (International Journal of Medical Research and Review, 2018)
Introduction: Solid pseudopapillary neoplasms (SPN/FRANTZ TUMOUR) of the pancreas are rare neoplasms of low grade malignant potential which were first described in 1959 by Frantz. These account for 0.13–2.7% of pancreatic neoplasms and approximately 13% of surgically resected cystic lesions of the pancreas. We present our experience with these rare tumors.Methods: Total 406 patients with pancreatic tumours were admitted in our department during the 10year period (Between 2007 and 2017) were reviewed, only 18 were diagnosed as having SPN(4.4%). Clinico-pathological details, intervention done and follow up of all the cases were studied and reported here.Results: 17 patients were woman and1was Man with median age of 23 years (range 11 to 54 years). The tumor size ranged from 3.8 to17cm (average 6.4 cm).12 patients presented with pain in the abdomen, 4 presented with a painless mass, 1 was detected incidentally and1presented with Malena. In 7 patients the tumor was in the pancreatic head, in 3 it was in the neck, and in the remaining 8 it is in the body and tail. CECT was done in all cases. 8 patients under went Distal pancreatectomy with splenectomy, 1 underwent a PPPD, 6 patients required classical Whipple operation. 3 underwent central pancreatectomy. Immuno histochemistry showed positivity for beta catenin, vimentin, PR receptor and chromogranin negativity. All 18 patients were free of disease in a median follow- up period of 32 months (range 6 – 84) months.Conclusion: SPNs are rare neoplasms, typically affecting young women without notable symptoms, with a low malignant potential but excellent prognosis. Radical surgical resection with clear margins is the treatment of choice.